Prevalence and risk factors associated with latent tuberculosis infection among household contacts of smear positive pulmonary tuberculosis patients in South India. Issue 12 (26th October 2021) - Krishnamoorthy, Yuvaraj; Ezhumalai, Komala; Murali, Sharan; Rajaa, Sathish; Jose, Maria; Sathishkumar, Abilasha; Soundappan, Govindarajan; Horsburgh, Charles; Hochberg, Natasha; Johnson, William Evan; Knudsen, Selby; Salgame, Padmini; et al.
Abstract: Objective: We aimed to determine the prevalence and find the risk factors associated with latent tuberculosis infection (LTBI) among the household contacts (HHC) of pulmonary TB patients. Methods: This cohort study was conducted from 2014 to 2019. Pretested standardised questionnaires and tools were used for data collection. The prevalence of LTBI among HHCs of TB patients was summarised as proportion with 95% confidence interval (CI). Mixed‐effects generalised linear modelling function ( meglm ) in STATA with family Poisson and log link was performed to find the factors associated with LTBI. Results: In total, 1523 HHC of pulmonary TB patients were included in the study. Almost all HHC shared their residence with the index case (IC) for more than a year; 25% shared the same bed with the IC. The prevalence of LTBI among the HHC of TB patients was 52.6% (95% CI: 50.1–55.1%). In an adjusted model, we found that among HHC belonging to the age group of 19–64 years (aIRR = 1.2; 95% CI: 1.1–1.3; p ‐value: 0.02), to the age group >65 years (aIRR = 1.4, 95% CI: 1.1–1.9, p ‐value: 0.02) and sharing the same bed with the IC (aIRR = 1.2, 95% CI: 1.1–1.3, p value: 0.04) were independent determinants of LTBI among the HHC. Conclusion: One in two household contacts of TB patients have latent tuberculosis infection. This underscores the need of targeted contact screening strategies, effective contact tracing and testing using standardised methods in high TB burden settings.